2022
DOI: 10.1002/deo2.200
|View full text |Cite
|
Sign up to set email alerts
|

A novel endoscopic finding of a scratch sign is useful for evaluating the Helicobacter pylori infection status

Abstract: Objectives During esophagogastroduodenoscopy, a red linear scrape‐like appearance with white deposits sometimes appears on the gastric mucosa at the lower greater curvature of the gastric body, a finding we named the “scratch sign.” We aimed to clarify the clinical significance of this new endoscopic finding in the endoscopic evaluation of the Helicobacter pylori infection status. Methods Among patients who underwent esophagogastroduodenoscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…In a previous study, the scratch sign had a high specificity and positive predictive value for indicating H. pylori-negative status, as only one patient was infected in the group with the scratch sign. 9 However, in our study, we found the number of 24 patients with current infections had scratch sign (Table 2) and patients with scratch sign had significantly lower rate of sticky mucus (0.7% vs. 20.4%, P<0.001). These findings were also shown in multivariate analysis, which found the only sticky mucus was significantly lowered the risk of scratch sign (Table 5).…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…In a previous study, the scratch sign had a high specificity and positive predictive value for indicating H. pylori-negative status, as only one patient was infected in the group with the scratch sign. 9 However, in our study, we found the number of 24 patients with current infections had scratch sign (Table 2) and patients with scratch sign had significantly lower rate of sticky mucus (0.7% vs. 20.4%, P<0.001). These findings were also shown in multivariate analysis, which found the only sticky mucus was significantly lowered the risk of scratch sign (Table 5).…”
Section: Discussioncontrasting
confidence: 52%
“…Yada et al 9 previously reported a significant association between a negative scratch sign and higher degrees of mucosal lesions, such as atrophy, intestinal metaplasia, enlarged folds, and diffuse redness, which all contribute to the Kyoto score. In our study, we also observed significant differences in the Kyoto score between patients with and without the scratch sign (1.7 vs. 3.3, P<0.001), reflecting similar findings.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations